Explaining the COVID19 mortality growth rate: an empirical analysis of Israeli cities - Arbel, Yuval; Arbel, Yifat; Kerner, Amichai; Kerner, Miryam (Frontiers in Public Health, 2025)
BackgroundThe severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an infectious virus, which has generated a global pandemic. Since December 20, 2020, Israel was one of the first countries to vaccinate its population. This study analyzes the weight of four covariates on a daily mortality growth rate from SARS-COV2 virus. These include population size, median age, a socio-economic ranking at a city level, a date variable and a dummy variable that equals 1 for post-vaccination and 0 for pre-vaccination era.MethodRegression analysis, where each variable is converted to the standard normal distribution function. This methodology permits the estimation of variations in daily mortality growth rates, where all the covariates are given in comparable units of measurement (one standard deviation). Consequently, the coefficients of this regression have to be measured as absolute value weights.ResultsFindings suggest a rise in projected mortality growth rate with population-size and median age, and a drop with socio-economic ranking and vaccination availability. Of the four investigated covariates, population size and median age of the city have the highest weight, whereas socio-economic ranking and vaccination availability have the lowest weight.ConclusionsIn an effort to reduce the mortality of severe coronavirus disease (COVID19) patients, greater priority should be given to larger cities with a relatively older population profile. In particular, policies should strive for better coordination at a municipal level between health and municipal and welfare services, particularly in large cities.